2022
DOI: 10.1037/str0000261
|View full text |Cite
|
Sign up to set email alerts
|

Distress in the workplace: Characterizing the relationship of burnout measures to the Occupational Depression Inventory.

Abstract: Burnout has been found to problematically overlap with depression. However, the generalizability of this finding remains disputed. This study examined burnout–depression overlap using the recently developed Occupational Depression Inventory (ODI) and two burnout measures, the Maslach Burnout Inventory (MBI) and the Copenhagen Burnout Inventory (CBI). The study involved two teacher samples employed in France (N = 1,450) and New Zealand (N = 492). We found the correlations of the ODI with (a) the MBI’s emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, a study analyzing the effects of patient safety programs in high-hazard workplaces, showed that implementing educational curricula for safety policies, decreased safety events. 24 Similar training could be provided for health crises to limit risks from burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study analyzing the effects of patient safety programs in high-hazard workplaces, showed that implementing educational curricula for safety policies, decreased safety events. 24 Similar training could be provided for health crises to limit risks from burnout.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of preparedness is surprising considering how prevalent burnout is among health care workers and emphasizes the need for better formal and informal training of administrators. For example, a study analyzing the effects of patient safety programs in high‐hazard workplaces, showed that implementing educational curricula for safety policies, decreased safety events 24 . Similar training could be provided for health crises to limit risks from burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our study did not reexamine the overlap between burnout and depression. Fortunately, this issue has been addressed extensively in past research ( 4 , 46 , 49 52 ), including ODI-based research ( 17 , 21 ). The advantages of relying on the construct of (occupational) depression have been discussed on many occasions ( 12 , 22 , 23 , 53 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its criterion validity and nomological network, occupational depression has been linked to a variety of job-related and context-free variables, including work engagement, job satisfaction, social support at work, job autonomy, trait anxiety, general health status, and objective cognitive performance ( 8 , 13 16 ). Furthermore, the instrument has served to clarify the controversial issue of burnout-depression overlap ( 17 , 21 ). ODI-based research has carried further the notion that burnout symptoms are part of a depressive syndrome and do not reflect a unique or distinct entity.…”
Section: Introductionmentioning
confidence: 99%
“…The ODI has demonstrated criterion validity in relation to a variety of variables, including work-life characteristics (e.g., interpersonal conflict at work, job incivility, unreasonable work tasks, unnecessary work tasks, work overload, social support at work, job autonomy, skill development, job recognition, job meaningfulness), general health status, and objective cognitive performance ( Bianchi and Schonfeld, 2021a , 2022 ; Hill et al, 2021 ; Bianchi et al, 2022a ; Schonfeld and Bianchi, 2022 ). An ODI-based study involving a deep-learning framework recently found occupational depression to be (a) negatively linked to companies’ stock growth and (b) positively linked to states’ economic deprivation ( Sen et al, 2022 ).…”
Section: Addressing Job-related Distress Differentlymentioning
confidence: 99%